Does adoption of an evidence‐based practice lead to job turnover? Results from a randomized trial. Issue 4 (24th December 2019) - Whitaker, Daniel J.; Lyons, Matthew; Weeks, Erin A.; Hayat, Matthew J.; Self‐Brown, Shannon; Zahidi, Rabab
Abstract: It is important to understand the impact of implementation of evidence‐based practices (EBPs) on the workforce. EBP implementation can increase job demands, stress, and burnout, and may thereby exacerbate turnover. This study examined the effects of implementation of an EBP on turnover among staff at nine child welfare agencies. A total of 102 providers were randomized to either adopt an EBP, SafeCare ©, or continue providing services as usual. Participants completed a baseline survey assessing demographics, attitudes toward EBPs, and organizational functioning, and provider turnover was recorded for up to 18 months following implementation. The overall turnover rate was 35%, but did not differ by EBP assignment (odds ratio [OR] = 1.27; 95% confidence interval [0.66, 2.45]). Variables associated with turnover included age (OR = 0.92), years since degree completion (OR = 0.94), prior exposure to EBP (OR = 3.91), believing that adopting an EBP was burdensome (OR = 0.52), and motivation for change (OR = 0.89). EBP assignment moderated two aspects of negative attitudes toward EBP (divergence and monitoring) to predict turnover; those attitudes were only positively related to turnover for individuals assigned to the EBP (OR = 1.46, 1.16). Implications of the findings for implementation are discussed.